Soluble β-Amyloid Oligomers Selectively Upregulate TRPC3 in Excitatory Neurons via Calcineurin-Coupled NFAT - Zhengjun Wang; Dongyi Ding; Jiaxing Wang; Ling Chen; Qingming Dong; Moumita Khamrai; Yuyang Zhou; Akihiro Ishii; Kazuko Sakata; Wei Li; Jianyang Du; Thirumalini Vaithianathan; et al. (Cells)
To investigate how dysregulated transient receptor potential canonical channels (TRPCs) are associated with Alzheimer’s disease (AD), we challenged primary neurons with amyloid-β (Aβ). Both the naturally secreted or synthetic Aβ oligomers (AβOs) induced long-lasting increased TRPC3 and downregulated the TRPC6 expression in mature excitatory neurons (CaMKIIα-high) via a Ca2+-dependent calcineurin-coupled NFAT transcriptionally and calpain-mediated protein degradation, respectively. The TRPC3 expression was also found to be upregulated in pyramidal neurons of human AD brains. The selective downregulation of the Trpc6 gene induced synaptotoxicity, while no significant effect was observed from the Trpc3-targeting siRNA, suggesting potentially differential roles of TRPC3 and 6 in modulating the synaptic morphology and functions. Electrophysiological recordings of mouse hippocampal slices overexpressing TRPC3 revealed increased neuronal hyperactivity upon the TRPC3 channel activation by its agonist. Furthermore, the AβO-mediated synaptotoxicity appeared to be positively correlated with the degrees of the induced dendritic Ca2+ flux in neurons, which was completely prevented by the co-treatment with two pyrazole-based TRPC3-selective antagonists Pyr3 or Pyr10. Taken together, our findings suggest that the aberrantly upregulated TRPC3 is another ion channel critically contributing to the process of AβO-induced Ca2+ overload, neuronal hyperexcitation, and synaptotoxicity, thus representing a potential therapeutic target of AD.